1997
DOI: 10.1088/0741-3335/39/8/007
|View full text |Cite
|
Sign up to set email alerts
|

Optimal condition for oscillating field current drive in a bootstrapped tokamak

Abstract: A simple physical form of the optimal condition for oscillating field current drive (OFCD) in a bootstrapped tokamak is given. The results of the analysis suggest that the required OFCD driving frequency can be reduced in a bootstrapped tokamak directly in proportion to the reduction in the OFCD fraction of the total toroidal current, while the total required poloidal magnetic flux content is independent of the OFCD driving frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Kessel et al [1] showed that, with the stabilizing effect of an ideally conducting wall, high normalized beta can be achieved at bootstrap fractions close to 100%. On the other hand, in the absence of wall stabilization, the beta limits are rather modest if the bootstrap fraction is significant [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kessel et al [1] showed that, with the stabilizing effect of an ideally conducting wall, high normalized beta can be achieved at bootstrap fractions close to 100%. On the other hand, in the absence of wall stabilization, the beta limits are rather modest if the bootstrap fraction is significant [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Before discussing the results of the optimization, it is worthwhile to recall the difficulty in achieving simultaneously high beta and a high bootstrap fraction [16,17]. Reference [17] shows that the product of the bootstrap fraction and beta is limited by where c geom 0.1(1 + κ 2 ) is a geometrical (and weakly profile dependent) factor related to the efficiency of bootstrap current generation, κ the elongation, β N = β(%)/I N the normalized beta and I N = I p (MA)/(a(m)B 0 (T)) the normalized plasma current.…”
Section: Introductionmentioning
confidence: 99%